Effective Counseling and Behavior Control in Secondary Schools in Kano State, Nigeria. - Sani, Bashir; Imbuki, Kennedy (NIU Journal of Social Sciences, 2017)
This article investigates the effectiveness of counseling services at some selected secondary schools in Kano State, Nigeria. The objectives are to, identify the adequacy of counselors, to determine their quality in terms of professional skill acquisition, and examine their roles in the schools. The study is survey, descriptive design was use, and the samples were obtained systematically. The instrument use in data collection is school counselor appraisal questionnaire (SCAQ) made by the researchers, the instrument has face and content validity and 4 Likert scale was use in the scoring. Descriptive statistics (Mean and standard deviation) were used in the analysis. The findings reveal that, the overall counselling services were low (Mean=1.311). The study concluded that, the counseling services rendered at secondary schools in Kano State is inadequate. Based on that, recommendations were proffered which suggests that, all secondary schools in Kano State should have functional counseling units, which is adequately equipped.